Lilin Dari Kulit Lemon (Citrus limon) Pencegah Demam Berdarah Di Desa Mayang Sukoharjo - Setya, Adhi Kumoro; Haryatmi, Dwi; Asmarani, Dewi Prantiannita Putri; Margareta, Rany Gina; Noviyanti, Mike; Waritsini, Belinda Khoirul (Pakis Journal Institute, 2025)
Every year dengue fever cases occur in Sukoharjo District. One of them occurred in Gatak Sub-district, where previously 3 residents were infected with the disease. There is one area, namely Mayang Village, where cadres and several residents cultivate lemons. In lemons, there is a skin that is often ignored but has potential that not many people are aware of, such as; preventing nausea, therapy and anti-insects, especially mosquitoes. One of the active substances contained in lemon peel, namely citronella, produces an aroma that insects do not like. The purpose of this community service is; providing knowledge about dengue fever, utilizing lemon peel into a health product, namely mosquito repellent aromatherapy candles and eliminating dengue fever. This community service activity was delivered using a counseling method equipped with a video screening of dengue fever and a demonstration of making mosquito repellent aromatherapy candles from lemons cultivated by the surrounding community. This activity was attended by 20 cadres from an initial target of 30 people. Participants were enthusiastic about the 7 questions presented, and in the results of the initial knowledge test and after the activity there was an increase in the participants' knowledge scores. In this activity, mosquito repellent aromatherapy candle products were produced which can be made or further developed into sales products.